A Requirements Engineering Process for IoT Systems - da Silva, Danyllo Valente; Gonçalves, Taisa Guidini; da Rocha, Ana Regina Cavalcanti (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Nowadays there is a great interest in IoT systems and many applications take advantage of this technology. The elicitation, specification and management of requirements for IoT systems present new challenges to requirements engineering. There is a lack of systematic approaches to the development of IoT applications and more specifically for IoT-based requirements engineering. To fill this gap this paper presents the definition of a Requirements Engineering process for IoT systems. This process is a tailored and harmonized version of the following processes of ISO IEC/IEEE 12207:2017 aiming to accomplish the needs of IoT systems: Business or Mission Analysis process, Stakeholder Needs and Requirements Definition process and System/Software Requirements Definition process.